Effect of Maturity Stages on the Nutritional Content of Hygrophila spinosa and Chenopodium album Leaves - Pal, A. D.; Basistha, R. (Journal of Scientific Research, 2021)
Urbanization has impacted the knowledge and use of traditional leafy vegetables. The present investigation is conducted to understand the importance of edible leaves and the variation in their nutritional content at different stages of maturity. Hygrophila spinosa and Chenopodium album leaves have been selected owing to their economic cost, accessibility, and utilization within the population. A leaf undergoes several physiological and metabolic changes during maturity, which may affect its biochemical content. Hence, the samples have been analyzed for their nutritional composition at distinct stages (I to IV) of maturity based on the length of the leaf post-germination. Results revealed that both samples possessed the highest content of nutrients, including carbohydrates, proteins, minerals, β carotene, and vitamin C at stage 1 compared to the older stages. Alteration in metabolic patterns and environmental influences during various phases may be responsible for this effect. Stage I manifested the notable existence of essential phytonutrients and the diminished presence of potent anti-nutrients. Moreover, a significant percentage of micronutrients are found to be available post in vitro gastrointestinal digestion. The study highlights the importance of consuming young edible leaves. Regular dietary incorporation of the same may lead to alleviation of nutrient deficiency disorders and food insecurity.